(untitled) (The Research of Medical Science Review, 2025)
Objective: This study evaluates the impact of an intervention on glycemic control, serum uric acid (SUA) levels, and body weight in patients with type 2 diabetes mellitus (T2DM) over a 3-month period, comparing outcomes between an Active Group and a Control Group. Methods: A total of 70 patients with T2DM were randomly divided into two groups: Active (n=35) and Control (n=35). Key parameters, including HbA1c, SUA levels, and body mass index (BMI), were assessed at baseline and after 3 months. Statistical analyses, including paired and independent t-tests, were conducted to evaluate within- and between-group differences. Proportions achieving clinical targets, such as HbA1c < 7%, were analyzed using chi-square and Fisher’s exact tests. Results: The Active Group demonstrated significant improvements compared to the Control Group. HbA1c levels decreased by -0.75% in the Active Group versus -0.06% in the Control Group (p < 0.001). SUA levels reduced by -0.73 mg/dL in the Active Group compared to -0.21 mg/dL in the Control Group (p < 0.01). BMI decreased by -0.79 kg/m² in the Active Group, while the Control Group remained stable (+0.04 kg/m², p < 0.001). A higher proportion of patients in the Active Group achieved HbA1c < 7% (45.7% vs. 11.4%, p < 0.001) and SUA < 6 mg/dL (34.3% vs. 5.7%, p < 0.01). The intervention was associated with significant metabolic and anti-inflammatory benefits. Conclusion: The intervention demonstrated superior effectiveness in improving glycemic control, lowering SUA levels, and promoting weight loss in patients with T2DM. These findings support its role as a comprehensive treatment option targeting multiple metabolic parameters. Further studies are warranted to confirm long-term benefits and broader applicability.